Understanding the role of colon-specific microparticles based on retrograded starch/pectin in the delivery of chitosan nanoparticles along the gastrointestinal tract - dos Santos, Aline Martins [UNESP]; Meneguin, Andréia Bagliotti [UNESP]; Akhter, Dewan Taslima; Fletcher, Nicholas; Houston, Zachary H.; Bell, Craig; Thurecht, Kristofer J.; Gremião, Maria Palmira Daflon [UNESP] (Elsevier, 2021)
The encapsulation of nanoparticles within microparticles designed for specific delivery to the colon is a relevant strategy to avoid premature degradation or release of nanoparticles during their passage through the stomach and upper gastrointestinal tract (GIT), allowing the targeted delivery of chemotherapeutics to the colon after oral administration. Here, we designed an oral multiparticulate system to achieve targeted release in the colon. In this sense, chitosan nanoparticles (CS NPs) encapsulated with 5-fluorouracil (5-FU) and incorporated into retrograded starch and pectin (RS/P) microparticles were developed and their in vivo distribution along the mouse GIT after oral administration was monitored using multispectral optical imaging. In vitro release studies revealed that the encapsulation of CS NPs into RS/P microparticles promoted greater control of 5-FU release rates, with a significant reduction (53%) in acid media that might replicate that found in the stomach following oral administration. The evaluation of the in vivo biodistribution of the CS NPs in mice showed a faster clearance in the distribution pattern along the mouse GIT, i.e., a shorter transit time of CS NPs compared to CS NPs-loaded RS/P microparticles. Additionally, CS NPs alone showed non-specific absorption into the blood-stream with associated kidney accumulation, while for the CS NPs-loaded RS/P microparticles no significant accumulation was observed in blood or major clearance organs. This suggests the specific degradability of RS/P by the colon microbiota appears to have been decisive in the higher protection of the CS NPs along the GIT until release in the colon, preventing unwanted absorption into the bloodstream and major organs following oral administration. Our findings represent a proof of concept for the use of RS/P microparticles as potential carriers for delivering drug-loaded nanoparticles to the colon and this work will contribute to the development of oral-systems for colorectal cancer therapy.
Keywords: Biodistribution; Chitosan; Colon-specific delivery; Microparticles; Nanoparticles; Oral drug delivery; Pectin; Retrograded starch